Short Review on recent solar PV policies in Malaysia - Husain A.A.F.; Ahmad Phesal M.H.; Abdul Kadir M.Z.; Ungku Amirulddin U.A. (EDP Sciences, 2023)
Cost effectiveness; Developing countries; Economic and social effects; Fossil fuels; Solar power generation; Cost effective; Economic growths; Energy productions; Harmful effects; Primary roots; Pv technologies; Rapid growth; Solar energy systems; Solar energy